The role of salinity as an environmental filtering factor in the determination of the Diptera taxonomic composition in the Crimean waters - Shadrin Nickolai V.; Belyakov Victor P.; Bazhora Alexandra I.; Anufriieva Elena V. (Knowledge and Management of Aquatic Ecosystems, 2019)
Salinity is one of the most important factors in aquatic ecosystems, but its filtering role in the Diptera community species composition is still poorly studied. This issue was studied in the diverse Crimean water bodies. A total of 425 samples were collected from freshwater to hypersaline waters. In 73% of the 425 samples examined, representatives of Diptera were found; their larvae and pupae belonged to seven families. Сhironomid species composition was analyzed in 47 samples. The most common were Chironomidae, which were in 94% of samples with Diptera, Ceratopoganidae were in 8% of samples, Ephydridae were in 5% of samples, Simuliidae were in 4% of samples, Culicidae and Chaoboridae were in 4% of samples, and Syrphidae was in only one sample. A total of 14 Chironomidae genera and 21 species and forms were found; 9 of them are new for Crimea. Reduction of the dominance variants in the community, as well as the number of chironomid species, with increasing salinity may indicate an increase in the filtering role of salinity in the Diptera community species composition that is still poorly studied.